Age- and gender-specific physical characteristics of youth alpine skiers with different skiing ability - Wurth, J. J.; Rimer, E. G. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2014)
Understanding which physical characteristics separate youth alpine skiers of differing age and ability can assist practitioners in early talent identification (1). This study compared age and gender specific physical abilities of youth alpine ski racers with their coaches` ratings of overall skiing ability.